People with disabilities in capixaba schools after 1964: Exception issues - Jesus, Denise Meyrelles; Simões, Regina Helena Silva; Luiz, Miriã Lúcia (Education Policy Analysis Archives, 2019)
In Brazil, from the 1950s to 1970s, the term “exceptional” was used to define people with disabilities as a counterpoint to a so-called “normal” human being. On the other hand, the term “exception regime” defined the post-1964 coup dictatorial government, which opposed the democratic republican regime. Based on the analysis of legislative documents, school records, reports on training internships in audiovisual resources, curricular proposals and demonstration schools, this article investigates the production of these exceptionalities and their consequences in school attendance for people with disabilities in the state of Espírito Santo during the dictatorial period (1964-1985). In this period, a bifronted movement was produced: in public education, the segregation of “exceptional” pupils - apparently supported by technical-pedagogical arguments - overshadowed social and economic factors that conditioned exclusions inside and outside of schools; in the private sphere, the creation of philanthropic institutions disobliged the state of the attendance to the ones who demanded differentiated educational support. In the first case, the aim was to promote analyses and solutions ranging from the domain of audiovisual resources and teaching techniques by teachers up to the organization of classes according to learning “levels” and “capacities” of the children judged “exceptional”. In the second case, basic principles of citizenship were denied.